Application of a multi-phase multi-morphology crystallization model to isotactic polypropylenes with different molecular weight distributions. (December 2017) - Troisi, E.M.; Arntz, S.A.J.J.; Roozemond, P.C.; Tsou, A.H.; Peters, G.W.M.
Graphical abstract: Highlights: Pressure and flow effects on crystallization of different MWD iPPs studied using extended PVT. Rheology and crystallization were measured and used as input for a model. Good agreement between model and experiments for crystallization T and phase content. Investigated iPPs didn't show presence of β-phase in disagreement with the model. Abstract: Flow-induced crystallization at elevated pressure of a set of metallocene isotactic polypropylenes (iPP) possessing different molecular weight distributions is studied using extended dilatometry experiments in an apparatus able to apply elevated pressure (up to 1200 bar) and strong shear flow (shear rates up to 180 s −1 ). The effect of flow on the crystallization temperature was quantified and the samples were analyzed using X-ray diffraction to measure the relative amounts of different crystal phases. The experimental results were used to test a flow induced crystallization model framework recently developed in our group which can describe the complex crystallization behavior of iPP and includes formation of multiple morphologies (spherulites, shish-kebab structure with lamellar branching) and crystal phases ( α, β and γ ). Almost all model parameters were left unchanged, except for the temperature description of the quiescent crystal growth rate and nucleation density (experimentally measured using optical microscopy) and an extra parameter which takes into account the fraction of high molecular weight for the creation of flow-induced nuclei. The model describes rather good the experimentally observed trends for what regards crystallization temperature and amount of α and γ -phase but substantial discrepancies were found in the amount of β -phase formed. This could be related to the presence of 2, 1 insertion errors in metallocene samples which could inhibit the formation of this crystal phase.